2013
DOI: 10.1080/00071668.2013.767439
|View full text |Cite
|
Sign up to set email alerts
|

The phytoestrogen daidzein may affect reproductive performance of Zhedong White geese by regulating gene mRNA levels in the HPG axis

Abstract: 1. The effect of daidzein, a naturally occurring phytoestrogen, on the reproductive performance of 120 female Zhedong White geese was determined. The geese were divided into 4 groups which were fed on diets containing 0 (Control), 10 (Da1), 20 (Da2) and 30 (Da3) mg daidzein per kg diet. Egg production and weight, fertility and hatchability rates, concentrations of estradiol (E2), triiodothyronine (T3), progesterone (P4), thyroxine (T4) and growth hormone (GH) in serum, and mRNA levels of gonadotropin releasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 26 publications
4
22
1
Order By: Relevance
“…In particular, only 65 DEGs were identified between high-and low egg production groups within LG. Because the reproductive performance of goose is generally thought to be regulated by the HPG axis [38,39], our results may suggest that the hypothalamus and pituitary should be the key organs controlling egg production performance in LG. Moreover, the expression difference in the DEGs of the neuroactive ligand-receptor interaction pathway was found in the SWG group.…”
Section: Discussionmentioning
confidence: 90%
“…In particular, only 65 DEGs were identified between high-and low egg production groups within LG. Because the reproductive performance of goose is generally thought to be regulated by the HPG axis [38,39], our results may suggest that the hypothalamus and pituitary should be the key organs controlling egg production performance in LG. Moreover, the expression difference in the DEGs of the neuroactive ligand-receptor interaction pathway was found in the SWG group.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, Shi et al (2013) reported that feeding ISF to laying hens at 59 weeks of age showed an increase in egg production. Moreover, dietary ISF daidzein at 10, 20, and 30 mg/kg improved fertility and egg weight (Zhao et al, 2013). Also, a diet supplemented with ISF daidzein for Shaoxing duck breeder significantly enhanced the productive performance during late laying stage (Zhao et al, 2005), and the same improved laying performance, and eggshell quality were observed in post-peak laying stage of hens (Ni et al, 2007).…”
Section: Introductionmentioning
confidence: 79%
“…The Zhedong white goose, characterized by strict seasonality, a high tendency to broodiness and incubation, and a low rate of egg laying, is one of the classical seasonal reproductive animals in China1. They have 3 or 4 laying cycles (Laying-Broodiness-Recovery) per year, and their laying periods are from October to April of the following year in Zhejiang province, China.…”
mentioning
confidence: 99%